Hegel on being : quanity and measure in Hegel's 'Science of Logic' Vol - 2 - Houlgate, Stephen (New York, NY, USA : Bloomsbury Academic, 2022)
"Hegel on Being provides an authoritative treatment of Hegel's entire logic of being. Stephen Houlgate presents the Science of Logic as an important and neglected text within Hegel's oeuvre that should hold a more significant place in the history of philosophy. In the Science of Logic, Hegel set forth a distinctive conception of the most fundamental forms of being through ideas on quality, quantity and measure. Exploring the full trajectory of Hegel's logic of being from quality to measure, this two-volume work by preeminent Hegel scholar, Houlgate situates Hegel's text in relation to the work of Plato, Aristotle, Descartes, Spinoza, Kant, and Frege. Volume I: Quality and the Birth of Quantity in Hegel's 'Science of Logic' covers all material on the purpose and method of Hegel's dialectical logic and charts the crucial transition from the concept of quality to that of quantity, as well as providing an original account of Hegel's critique of Kant's antinomies across two chapters. Volume II: Quantity and Measure in Hegel's 'Science of Logic' continues the discussion of Hegel's logic of being and considers all aspects of quantity and measure in his logic, including his basic categories of being, writings on calculus, philosophy of mathematics, as well as a comparative study of Hegel and Frege's approach to logic. Lucidly written, with characteristic philosophical depth and analysis, Houlgate's Hegel on Being explicates one of Hegel's most complex works, providing a vital reference for a generation of Hegel scholars and a major contribution to the literature on 19th century German philosophy"--
Vol. 1. Quality and the birth of quantity in Hegel's logic -- Vol. 2. Quantity and measure in Hegel's logic.
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Logic; Logic -- Wissenschaft der Logik (Hegel, Georg Wilhelm Friedrich)